2020
DOI: 10.3748/wjg.v26.i25.3542
|View full text |Cite
|
Sign up to set email alerts
|

Practical review for diagnosis and clinical management of perihilar cholangiocarcinoma

Abstract: Cholangiocarcinoma (CCC) is the most aggressive malignant tumor of the biliary tract. Perihilar CCC (pCCC) is the most common CCC and is burdened by a complicated diagnostic iter and its anatomical location makes surgical approach burden by poor results. Besides its clinical presentation, a multimodal diagnostic approach should be carried on by a tertiary specialized center to avoid miss-diagnosis. Preoperative staging must consider the extent of liver resection to avoid post-surgical hepatic failure. During s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
6

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 139 publications
0
32
0
6
Order By: Relevance
“…Complete resection is the most effective treatment for this kind of malignancy, as the role of adjuvant chemotherapy and radiotherapy remains controversial in medical literature: specifically, the studies that successfully demonstrated advantages of adjuvant chemoradiation therapy evidenced a survival benefit of only a few months. Resectability of perihilar cholangiocarcinomas remains limited (<50 %) due to late presentation, and should be accurately evaluated accounting tumour extension, patient status and liver function [8] . The complexity surgical treatment and clinical management mandates surgical eligibility to be assessed in high-volume and expertise centres, which are characterized by lower failure-to-rescue from surgical complications and consequently lower in-hospital and 3-months mortality [9] .…”
Section: Discussionmentioning
confidence: 99%
“…Complete resection is the most effective treatment for this kind of malignancy, as the role of adjuvant chemotherapy and radiotherapy remains controversial in medical literature: specifically, the studies that successfully demonstrated advantages of adjuvant chemoradiation therapy evidenced a survival benefit of only a few months. Resectability of perihilar cholangiocarcinomas remains limited (<50 %) due to late presentation, and should be accurately evaluated accounting tumour extension, patient status and liver function [8] . The complexity surgical treatment and clinical management mandates surgical eligibility to be assessed in high-volume and expertise centres, which are characterized by lower failure-to-rescue from surgical complications and consequently lower in-hospital and 3-months mortality [9] .…”
Section: Discussionmentioning
confidence: 99%
“…Radical resection is the state-of-the art therapy and provides a 5-year OS of between 20% and 50% in cases with R0 resection[ 97 , 98 ]. However, a significant proportion of patients cannot undergo resection either because of distant metastases, a locally advanced tumor, quality of liver parenchyma, or underlying liver disease[ 99 ]. Hence, liver transplantation might be the only remaining curative option for those patients.…”
Section: Primary Liver Cancermentioning
confidence: 99%
“…The patient with HBO generally presents cholestasis and obstructive jaundice, in this setting the first-line imaging technique is classically an abdominal ultrasound (US). Although it is a useful tool in the initial management, US is an operator-dependent technique and is burdened by low sensitivity and specificity [ 6 ]. Multidetector computed tomography (CT), magnetic resonance imaging (MRI), and magnetic resonance cholangiopancreatography (MRCP) are generally required to perform an accurate diagnosis.…”
Section: Diagnostic Approach In Hbomentioning
confidence: 99%
“…Endoscopic Retrograde Cholangio-Pancreatography (ERCP) is nowadays considered a therapeutic procedure, however, during ERCP several diagnostic tools can be used—brush cytology, endobiliary biopsy, and cholangioscopy. Brush cytology is an easy procedure, routinely performed in suspicious biliary strictures, characterized by low sensitivity (ranges 20–40%) and high specificity (ranges 92–100%) [ 6 ]. The sensibility can be improved by performing multiple brushings during the same ERCP and performing fluorescence in situ hybridization (FISH) analysis on the sample [ 9 , 10 ].…”
Section: Diagnostic Approach In Hbomentioning
confidence: 99%